Loneliness in Brazil: a silent threat to Public Health - Hisrael Passarelli-Araújo (Cadernos de Saúde Pública)
Abstract: Loneliness has emerged as a significant Public Health issue, yet its impact in developing countries remains understudied. This study examines the growing concern regarding loneliness in Brazil and how aging, urbanization, and changes in family structure may erode traditional social supports and deepen loneliness across various groups. The study also assesses the challenges of measuring loneliness, given its subjective nature, and critically evaluates how well the Brazilian Unified National Health System (SUS) is equipped to address loneliness via community-based interventions and integrated healthcare strategies. The study suggests that loneliness is intensifying due to demographic changes as the population ages, becomes more urbanized, and experiences shifts in family structure. Although SUS employs community-focused health strategies and extensive care models to combat loneliness, it struggles with challenges like insufficient funding, high patient-to-professional ratios, and a fragmented healthcare system. This study emphasizes that loneliness cannot be resolved medically, such as with vaccine, but with strengthened social connections and community support. We advocate for a comprehensive approach that includes healthcare and cross-sector collaboration with the education, housing, and social services branches to tackle both the symptoms and root causes of loneliness, positioning it as a pressing Public Health priority.